2016
DOI: 10.1111/psyg.12174
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of cerebral glucose hypometabolism on positron emission tomography with electroconvulsive therapy in an elderly patient with a psychotic episode

Abstract: AB, a 74-year-old Caucasian woman, was admitted for acute onset of psychosis, anxiety, and cognitive impairment. Pharmacotherapy was unsuccessful and the patient was referred for electroconvulsive therapy (ECT). Pre-ECT, F-fluorodeoxyglucose-positron emission tomography (PET)/computed tomography showed extensive frontal, parietal, and temporal cortical hypometabolism suggestive of a neurodegenerative disease. After eight ECT sessions, the psychotic and anxiety symptoms as well as the cognitive impairment resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…At the time of writing, there was a notable paucity of literature addressing the specific use of acute ECT in the elderly with primary psychotic conditions, this being limited to one case series and five individual case reports, reporting a total of 10 patients (Kumagaya & Halliday, ). Similar to this case series, ECT was found to be highly effective in this group of patients, resulting in full or partial remission in eight and two patients, respectively (Hassamal et al, ; Kramer, ; Meyen et al, ; Selvadurai et al, ; Suzuki, Shindo, et al, ; Tang & Park, ). Studies of mixed age and diagnoses that have included elderly patients with treatment‐ and clozapine‐resistant primary psychotic conditions have also demonstrated improvements in the Brief Psychiatric Rating Scale (BPRS) (Suzuki, Awata, & Matsuoka, ; Tang & Ungvari, ; Tor et al, ), Clinical Global Impression (CGI) (Chiu, Lee, & Lee, ; Kales, Dequardo, & Tandon, ; Kaster et al, ; Tang & Ungvari, ), Positive and Negative Syndrome Scale (PANSS) (Kho et al, ), Global Assessment Scale (GAS) (Tang & Ungvari, ), Scale for the Assessment of Negative Symptoms (SANS) (Tang & Ungvari, ), and Global Assessment of Functioning (GAF) scores (Kales et al, ; Suzuki et al, ).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…At the time of writing, there was a notable paucity of literature addressing the specific use of acute ECT in the elderly with primary psychotic conditions, this being limited to one case series and five individual case reports, reporting a total of 10 patients (Kumagaya & Halliday, ). Similar to this case series, ECT was found to be highly effective in this group of patients, resulting in full or partial remission in eight and two patients, respectively (Hassamal et al, ; Kramer, ; Meyen et al, ; Selvadurai et al, ; Suzuki, Shindo, et al, ; Tang & Park, ). Studies of mixed age and diagnoses that have included elderly patients with treatment‐ and clozapine‐resistant primary psychotic conditions have also demonstrated improvements in the Brief Psychiatric Rating Scale (BPRS) (Suzuki, Awata, & Matsuoka, ; Tang & Ungvari, ; Tor et al, ), Clinical Global Impression (CGI) (Chiu, Lee, & Lee, ; Kales, Dequardo, & Tandon, ; Kaster et al, ; Tang & Ungvari, ), Positive and Negative Syndrome Scale (PANSS) (Kho et al, ), Global Assessment Scale (GAS) (Tang & Ungvari, ), Scale for the Assessment of Negative Symptoms (SANS) (Tang & Ungvari, ), and Global Assessment of Functioning (GAF) scores (Kales et al, ; Suzuki et al, ).…”
Section: Discussionsupporting
confidence: 69%
“…This is particularly significant given that most patients in this study received a substantial number of treatments. No severe adverse effects were likewise noted in studies specific to the elderly with psychotic conditions (Hassamal et al, ; Kramer, ; Meyen et al, ; Selvadurai et al, ; Suzuki, Takano, et al, ; Tang & Park, ). A comparative study of ECT safety in patients above and below the age of 60 did, however, show that adverse effects were more commonly experienced in late‐life patients; these were predominantly cardiovascular and cognitive in nature (Antosik‐Wojcinska & Swiecicki, ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The literature search yielded six studies focusing specifically on ECT efficacy in the elderly with primary psychotic conditions (Table 1). 5,[14][15][16][17][18] A further 17 studies included at least one patient older than 60 years of age within a mixed-age cohort, or a mixed-diagnoses cohort where outcomes specific to patients with primary psychotic conditions were reported (Table 2). 4,10,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]…”
Section: Resultsmentioning
confidence: 99%
“…After improving the patient’s symptoms through ECT, PET imaging showed that her brain metabolism was normal. Hassamal et al [ 43 ] adopted 18 F-FDG-PET/CT before ECT to show extensive hypometabolism in the frontal, parietal and temporal cortices. After eight sessions of ECT, symptoms of psychosis and anxiety symptoms as well as cognitive impairment were resolved.…”
Section: Brain Functional Imaging Study For Depression With Ectmentioning
confidence: 99%